Three levels of software applications for a digitalized additive manufacturing process chain - Ackermann, Sven; Kolb, Tobias; Tremel, Jan; Schmidt, Michael (11th CIRP Conference on Photonic Technologies [LANE 2020], 2020)
The further development of digital process-planning, -preparation and -analysis tools is crucial to increase efficiency and profitability of additive manufacturing (AM) systems. Therefore, we identified three distinct levels of software application along the AM process chain. On the machine level (1), sensor data is analyzed to notify the user about problems during the print, machine state, or even part quality. In a conventional manufacturing plant, a digital workflow through the whole process chain is state of the art. The integration of a digital workflow in AM is not fully given but necessary to connect all the steps of the organizational level (2) efficiently. Simulations of parts, machines and the whole process chain in a digital twin (3) gather important feedback before printing, changing machine parameters or even ordering new machines. In this context, this contribution reports on current developments, challenges and future visions for implementing a fully digital additive manufacturing process chain.<br
Keywords: Additive Manufacturing; digital process chain; digitalization; digital workflow; laser powder bed fusion